Comparative study of allelopathic potential of Lemon Grass (Cymbopogon citratus S.), Goose Grass (Eleusine indica L.), and Cogon Grass (Imperata cylindrica L.) on the germination of Pechay seeds (Brassica rapa) - Ilagan, Katrin S.; Mahinay, Teresa S. (Tacloban City Katrin S. Ilagan, 2014)
Allelopathy is the production of chemicals (allelochemicals) of a plant which can influence the growth and development of another plant that can be either negative by reducing germination or positive by increasing growth. This study was conducted to determine the allelopathic potential of the following grasses, Cymbopogon citratus, Eleusine indica and Imperata cylindrica on the germination of pechay (Brassica rapa) seeds and their allelopathic activities were compared. Leaves and culms of the three grass species were used for the extraction of allelochemicals. Extraction was done after the method of infusion (Fernandez 1990). Filter paper germination assay was the growth assay used. In this assay, four layers of Whatmann number one filter paper were placed in a petri dish and were irrigated with 10ml of the grass extracts. Ten pechay seeds were then placed in the petri dish. Results showed that seeds irrigated with I. cylindrica extracts have the lowest germination rate of B. rapa while those treated with E. indica extract have the highest germination rate. This seem to indicate that I. cylindrica has a higher allelopathic effect on B. rapa germination than E. indica and C. citratus. The results further revealed that all the three grass species investigated had significantly reduced the germination rate B. rapa seeds at 0.01 level of significance using One-way Analysis of Variance.
Undergraduate thesis (B.S. in Biology)--University of the Philippines, Tacloban.